Developing individual competencies profile and application to FPT corporation : M.A. Thesis: Business Administration - Trương, Vũ Thanh Thuỷ (Đại học Quốc gia Hà Nội, 2017)
M.A. Thesis. Business administration -- School of Business. Vietnam National University Hanoi, 2004